2018
DOI: 10.1177/0886260518801018
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Factors Associated With Interrupting the Transmission of Domestic Violence Among Adolescents

Abstract: Exposure to child maltreatment in the family-of-origin has consistently been linked to intimate partner violence (IPV) perpetration in adulthood. Although the concept of a cycle of violence presumes that the transmission of violence is expressed directly across generations, some protective factors such as social support, self-esteem, and relationship quality with parents may ultimately be influential in nonviolent behavior in adult relationships. Using the National Longitudinal Study of Adolescent Health data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
1
9
0
2
Order By: Relevance
“…To date, violence against women and violence manifestations within the context of romantic relationships is becoming a world global issue [ 3 , 4 , 38 ]. Specially worrying is the fact the IPV is starting earlier, with a larger number of adolescents involved in this kind of violence [ 5 , 6 , 7 ]. Adolescence intimate partner violence rates are increasing affecting now to more than half of all dating youth [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, violence against women and violence manifestations within the context of romantic relationships is becoming a world global issue [ 3 , 4 , 38 ]. Specially worrying is the fact the IPV is starting earlier, with a larger number of adolescents involved in this kind of violence [ 5 , 6 , 7 ]. Adolescence intimate partner violence rates are increasing affecting now to more than half of all dating youth [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing interest is being devoted to intimate partner violence (IPV), due to the severe physical, psychological, and social consequences associated, as well as the growing prevalence through the world [ 1 , 2 , 3 , 4 ]. This specific kind of violence that includes physical, verbal, and sexual violence has become a serious and prevalent problem, not only in adulthood but also in adolescence and into emerging adulthood [ 5 , 6 , 7 ]. For instance, The WHO Multi-country Study on Women’s Health and Domestic Violence against women revealed that women between 15 and 49 years old had suffer some kind of partner violence in percentages that ranged from 13 to 61 percent [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have consistently shown that childhood exposure to parental abuse is linked to their adulthood beliefs/behaviors related to wife abuse [ 23 , 24 ], although little is known about why many adults who were exposed to abusive childhood events do not continue the same pattern with their partners [ 26 ]. It is possible that higher education and an awareness of the risks associated with abuse, a person’s self-esteem, relationship quality, meaningful victim support system, gender-equitable environment, and suitable social control mechanism may de-motivate people to continue the abuse in adulthood even if they have experienced and internalized the abuse in their childhood [ 27 29 ]. A few studies based in Bangladesh have focused on the social learning of wife abuse and its social acceptance among people [ 7 , 30 ].…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Specifically, there was a high risk for anxiety, depression, stress, and trauma (Boeckel et al, 2017;Lyold, 2018;Silva et al, 2019), lower performance at school (McDonald et al, 2016), and behavioral problems including hostility, aggression, and delinquency for these children (Lyold, 2018;Paterson et al, 2008). Additionally, previous longitudinal studies claimed that the harmful effects of exposure to DV in childhood continued to manifest in adulthood (Cater et al, 2015;Genç et al, 2018;Miller-Graff et al, 2016). It might influence children's manners toward the use of violence and increase the odds of being a victim or perpetrator of violence in their romantic relationships (Eriksson & Mazerolle, 2015;Forke et al, 2018;Genç et al, 2018).…”
Section: Effects Of Early Experience Of Domestic Violencementioning
confidence: 99%
“…Previous research has reported that children's experience of violence in the home has been associated with various negative immediate and long-term effects that can be considered as serious damage to those children's emotional, psychological, as well as psychical wellbeing (Cater et al, 2015;Caykoylu et al, 2011;Maxwell et al, 2016). Additionally, violent acts observed or learned from the family can be transferred into an individual's adult life and lead them to become either being a perpetrator or victim of violence in their romantic relationship (Eriksson & Mazerolle, 2015;Forke et al, 2018;Genç et al, 2018;Genç, 2020).…”
Section: Introductionmentioning
confidence: 99%